A huge chest wall angiomatosis with pleural and rib invasion: A case report. Issue 49 (9th December 2022) - Wang, Yu-Chi; Lin, Yun-Nan; Chai, Chee-Yin; Li, Hsien-Pin; Chen, Yi-Ting; Kuo, Yur-Ren
Abstract : Rationale: Angiomatosis is a rare non-neoplastic proliferative vascular lesion that typically develops during childhood or adolescence with a female predominance. Management of angiomatosis is challenging because of the manifestation of a wide variety of lesions as well as their invasive and highly recurrent nature. Patient concerns: We report the case of a 74-year-old man who presented with a right lower back mass that persisted for a decade. The mass progressively enlarged and had been painful in the previous month. Diagnosis: Computed tomography (CT) revealed suspected lipomatous sarcoma with invasion of the ribs, pleurae, and lung parenchyma. The final pathological examination revealed angiomatosis. Interventions: The patient underwent wide composite excision of the tumor along with excision of the pleura and lung nodules in the right lower and middle lobes via video-assisted thoracoscopic surgery (VAST). Fasciocutaneous rotational flap reconstruction was performed immediately after the wide composite excision and video-assisted thoracoscopic surgery (VAST). Outcomes: The patient recovered uneventfully, was discharged without complications, and tolerated the daily activities well. Lessons: Angiomatosis is a rare benign vascular tumor that frequently mimics malignancy. Even if the patient profile does not match the reported epidemiology of this disease, differential diagnosis should be considered. Complete resection is the mainstay of treatment for the prevention of recurrence.